2022
DOI: 10.21467/preprints.381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Risk Factors and Refugee Children in Bangladesh

Abstract: In the Cox's Bazar refugee camps, around 855,000 Rohingya people live, with 54 percent of them being children. In Myanmar, these children were denied access to adequate healthcare, immunizations, food & nutrition, hygiene, and education. Since August 2017, when the Rohingya were forced to flee from Myanmar to Bangladesh due to the Myanmar military's brutality, they have become more vulnerable. Children were vulnerable to hunger and various infectious diseases as a result of the fighting and displacement, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Approximately 10% of women in the Rohingya community of Bangladesh are malnourished, and their immunity is deteriorating daily (Leidman et al, 2018). According to a recent study, the children in the camp settings are malnourished due to a lack of basic food (Parvin, 2022). Another study indicated that the majority of Rohingya children studied were underweight and wasted (Roy et al, 2022).…”
Section: Nutritional Health Of Rohingya Refugees During Covid-19 Pand...mentioning
confidence: 99%
“…Approximately 10% of women in the Rohingya community of Bangladesh are malnourished, and their immunity is deteriorating daily (Leidman et al, 2018). According to a recent study, the children in the camp settings are malnourished due to a lack of basic food (Parvin, 2022). Another study indicated that the majority of Rohingya children studied were underweight and wasted (Roy et al, 2022).…”
Section: Nutritional Health Of Rohingya Refugees During Covid-19 Pand...mentioning
confidence: 99%